The crisis of religious intolerance in contemporary Indonesia – a phenomenon of the Islamic housing industry and its impact on social life - Piosik, Monika (Wydawnictwa AGH, 2020)
In the last few years Indonesia has been experiencing a new wave of Muslim revival. In addition to the growing popularity of conservative and even radical Muslim ideologies such as Wahhabism and Salafism, this de facto multi-religious society is facing a strong trend towards religious segregation. Indonesians are looking for new forms of their religious manifestation and expressions of their piety. One of the most vivid examples of Muslim separation from other religions is the perumahan syariah, a new form of gated communities in Indonesia. The article describes the growing phenomenon of closed neighborhoods where residents' lives are restricted by Sharia law. The paper first describes the roots of the current religious revival and its impact on the social situation, then deepens the definition of gated communities in the context of perumahan syariah as well as controversies linked to the topic. In conclusion, the possible implications for social life in Indonesia are presented.

W ciągu ostatnich kilku lat Indonezja przeżywa religijne odrodzenie muzułmańskie. Oprócz rosnącej popularności konserwatywnych, a nawet radykalnych ideologii muzułmańskich, takich jak wahhabizm i salafizm, społeczeństwo de facto wieloreligijne stoi w obliczu silnego trendu segregacji religijnej. Indonezyjczycy poszukują nowych form manifestacji religijnej i wyrażania swojej pobożności. Jednym z najbardziej wyrazistych przykładów separacji muzułmanów od innych religii jest perumahan syariah – nowa forma zamkniętych osiedli w Indonezji. Artykuł opisuje narastające zjawisko zamkniętych dzielnic, gdzie życie mieszkańców jest regulowane przez prawo szariatu. W pierwszej części opisuję korzenie obecnego ożywienia religijnego i jego wpływ na sytuację społeczną. Następnie pogłębiam definicję zamkniętych wspólnot oraz kontrowersji związanych z tym tematem. W podsumowaniu przedstawiam możliwe implikacje tego fenomenu dla życia społecznego w Indonezji.
Kryzys tolerancji religijnej we współczesnej Indonezji – fenomen muzułmańskiego rynku nieruchomości i jego wpływ na życie społeczne
Studia Humanistyczne AGH
Keywords: Indonesia; gated communities; anthropology; Islam; radicalization; islam; Indonezja; zamknięte osiedla; antropologia; radykalizacja